2018
DOI: 10.1021/acsaelm.8b00001
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Controlled White Light Emission and Extraction in CdS/Black-Si Conical Heterojunctions

Abstract: The light emission characteristics of Si nanocrystallites on a chemically etched black-Si surface, coupled with its excellent light extraction feature of nanocone geometry is reported for potential use in future Si-based CMOS-compatible light-emitting applications. As a proof of concept, n-CdS/p+-black-Si conical-heterojunction arrays, fabricated by depositing n-CdS film on vertically standing nanoporous Si nanocones, exhibiting intense white light emission, have been studied. Si nanocone arrays of 1 to 3 μm h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…[1][2][3][4] Reducing the dimensions of Si structures below the excitonic Bohr radius of Si ($4.8 nm) results in light emission due to the quantum confinement effect (QCE). [5][6][7][8] Different approaches of light emission through the QCE have been reported to date based on Si nanowires, [9][10][11][12] nanocones, 13,14 colloidal nanocrystals, 15,16 and nanocrystals in the oxide matrix. 5,[17][18][19] Among them, Si nanocrystals (Si NCs) embedded into the SiO 2 matrix are most promising due to chemical stability and wavelength selective size-tunable photoluminescence (PL).…”
mentioning
confidence: 99%
“…[1][2][3][4] Reducing the dimensions of Si structures below the excitonic Bohr radius of Si ($4.8 nm) results in light emission due to the quantum confinement effect (QCE). [5][6][7][8] Different approaches of light emission through the QCE have been reported to date based on Si nanowires, [9][10][11][12] nanocones, 13,14 colloidal nanocrystals, 15,16 and nanocrystals in the oxide matrix. 5,[17][18][19] Among them, Si nanocrystals (Si NCs) embedded into the SiO 2 matrix are most promising due to chemical stability and wavelength selective size-tunable photoluminescence (PL).…”
mentioning
confidence: 99%
“…Recently, LEDs of different luminescence materials have been fabricated using the PLD technique. Sarkar et al [51] reported a white light emission from CdS/p + −black Si (CdS/p + −bSi) LED, manufactured by laser ablation of n-CdS thin film on a nanoporous Si nanocones fabricated subsequently by means of metal-assisted chemical etching technique. A detailed review of this publication is in Section 5.…”
Section: Overview Of Devices Fabricated Using Pldmentioning
confidence: 99%
“…The field emission scanning electron microscope (FESEM) cross-section image of the bSi fabricated on a Si substrate reported by Sarkar et al [51] is shown in Figure 9a. The FESEM micrograph revealed that the bSi formed vertical cone-shaped nanostructures of the diameter between 500 and 700 nm, height between 1 and 3 µM and tips of a few nanometers in diameter.…”
Section: Structure Morphologies and Luminescence Of Thin Films Deposited Using Pldmentioning
confidence: 99%
See 2 more Smart Citations